Cholesterol-lowering effects of oat β-glucan - Othman, Rgia A; Moghadasian, Mohammed H; Jones, Peter JH (Nutrition reviews, 2011)
Elevated total and low‐density lipoprotein (LDL) cholesterol levels are considered major risk factors for cardiovascular disease. Oat β‐glucan, a soluble dietary fiber that is found in the endosperm cell walls of oats, has generated considerable interest due to its cholesterol‐lowering properties. The United States Food and Drug Administration (FDA) approved a health claim for β‐glucan soluble fiber from oats for reducing plasma cholesterol levels and risk of heart disease in 1997. Similarly, in 2004 the United Kingdom Joint Health Claims Initiative (JHCI) allowed a cholesterol‐lowering health claim for oat β‐glucan. The present review aims to investigate if results from more recent studies are consistent with the original conclusions reached by the FDA and JHCI. Results of this analysis show that studies conducted during the past 13 years support the suggestion that intake of oat β‐glucan at daily doses of at least 3 g may reduce plasma total and low‐density lipoprotein (LDL) cholesterol levels by 5–10% in normocholesterolemic or hypercholesterolemic subjects. Studies described herein have shown that, on average, oat consumption is associated with 5% and 7% reductions in total and LDL cholesterol levels, respectively. Significant scientific agreement continues to support a relationship between oat β‐glucan and blood cholesterol levels, with newer data being consistent with earlier conclusions made by the FDA and JHCI.